AN IMAGINARY ALGORITHMIC PUBLIC: HOW MEDIA REPORT ON ￼SEARCH QUERY METRICS ￼ - Jobin, Anna (AoIR Selected Papers of Internet Research, 2015)
Web search engines provide search query metrics in different formats for different audiences, notably annual search query statistics by country, which are often reported on by traditional media outlets. These statistics present top-ranking query charts for different categories based on time and territoriality and are known as Google’s Year in Search (formerly: Zeitgeist). They are presented by Google as a simple algorithmic mirror of aggregated human interest. However, Gillespie (2014) argues that ’algorithms designed to offer relevant knowledge also offer ways of knowing.’ What ’ways of knowing’ are offered by annual search query metrics, and how are they accepted, ignored, perpetuated, or questioned by journalists of traditional media outlets? This paper answers these questions based on a qualitative study of national media and major newspapers reporting on Google’s Year in Search Switzerland over the last years. It specifically focuses on how the six political dimensions of public relevance algorithms (Gillespie, 2014) have been addressed. Based on Switzerland’s status as an officially multilingual country the paper also illustrates the marginalization of linguistic minorities as territoriality-based quantitative search query metrics cater to the majority by constructing, algorithmically, a national public of search users that does not exist as such.